2018
DOI: 10.1021/acs.macromol.8b01503
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and Segregation Behavior at the Submicrometer Scale of PCL/PEG Blends

Abstract: The crystallization and segregation behavior of immiscible polycaprolactone/poly­(ethylene glycol) PCL/PEG (50/50) blends was investigated using mainly resonance-enhanced atomic force microcopy coupled with infrared spectroscopy (AFM-IR) which allows a spatial resolution of the order of 30–50 nm. Chemical infrared images of the blends at different scales highlight their island-like spherulitic structures. The nanoscale IR spectra on both sides of the spherulitic interfaces are different. The polymer segregatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…Our study offers a better understanding of the long-term degradation of PCL-blend-PEG coatings. PEG and PCL are immiscible polymers and they phase-separate in the solid state, as recently reported in the literature [67][68][69]. Therefore, in an early stage, after the PCL-blend-PEG's immersion, the first released material is mainly identified as the water-soluble PEG component, while for long term immersion periods, residual products of insoluble CL oligomers result due to the slow degradation of the PCL [70].…”
Section: Coating Degradation Behaviormentioning
confidence: 62%
“…Our study offers a better understanding of the long-term degradation of PCL-blend-PEG coatings. PEG and PCL are immiscible polymers and they phase-separate in the solid state, as recently reported in the literature [67][68][69]. Therefore, in an early stage, after the PCL-blend-PEG's immersion, the first released material is mainly identified as the water-soluble PEG component, while for long term immersion periods, residual products of insoluble CL oligomers result due to the slow degradation of the PCL [70].…”
Section: Coating Degradation Behaviormentioning
confidence: 62%
“…Several investigations have been reported on the effect of industrial contaminants on the morphology, mechanical properties and structure of glove material. In previous works [15][16][17][18][19][20][21][22][23][24], we reported that polymers and composites [16][17][18][19][20]22,23,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] can be degraded by several aging agents such as heat, water, humidity, oxygen, ozone and various other environments factors [16][17][18][19][20][21][22][23][24]. The scission, crosslinking and plasticization of polymer networks may occur and led to severe deterioration of the mechanical and physicochemical properties of the material [42], which are quite important with regard their applications in various fields of mechanical engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have successfully used AFM-IR to shed light on some scientific questions related to: (i) the aging mechanism at the surface of organic coatings; 37 (ii) the complementary understanding of the aging mechanism of a polyester fiber; 38 (iii) the grafting of the polyvinyl pyridine-like polymeric film on a titanium nitride wafer; 39 and (iv) the crystallization behavior of immiscible 10 and miscible blends. 11 In this article, AFM-IR in combination with polarized optical microscopy (POM) are mainly used to investigate the transcrystallization phenomena of a PCL/PVC blend with the presence of a single milkweed fiber in terms of the crystal growth mechanism, spherulite morphology, and polymer diffusion.…”
Section: Introductionmentioning
confidence: 99%